2007
DOI: 10.1186/1471-2458-7-105
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and use of wireless telephones: a population-based study of Swedish children aged 7–14 years

Abstract: Background: Recent years have seen a rapid increase in the use of mobile phones and other sources of microwave radiation, raising concerns about possible adverse health effects. As children have longer expected lifetime exposures to microwaves from these devices than adults, who started to use them later in life, they are a group of special interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
52
1
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 10 publications
(13 reference statements)
14
52
1
3
Order By: Relevance
“…By the age of 13, most of our sample had used a mobile phone, which is comparable to Swedish data [Soderqvist et al, 2007]. We found that students who reported making or receiving more voice or SMS calls per week, and in particular more of both, demonstrated shorter response times on learning tasks, but less accurate working memory.…”
Section: Discussionsupporting
confidence: 79%
“…By the age of 13, most of our sample had used a mobile phone, which is comparable to Swedish data [Soderqvist et al, 2007]. We found that students who reported making or receiving more voice or SMS calls per week, and in particular more of both, demonstrated shorter response times on learning tasks, but less accurate working memory.…”
Section: Discussionsupporting
confidence: 79%
“…However, given that these pervious papers were written when mobile phone technology was fairly new to the society, it would not be fully appropriate to apply such suggestions to the current findings because mobile phones are very commonly used throughout the society today. Females generally spent more time on their mobile phones than males over all age groups, with a greater number of calls per day and a longer average time per call, which are consistent with results from previous studies [7,9,13,14]. These results may corroborate the possible existence of traditional gender role within the mobile culture, with females showing more interest towards the interactive side of communication technology, rather than the innovative counterparts [10].…”
Section: Discussionsupporting
confidence: 89%
“…Taking the still relatively short time for use of wireless phones on a broad scale (30,31) the results showing increasing brain tumour incidence may be early warning of future public health problems, especially considering the large deficit in the Swedish Cancer Registry. It is striking that during 2000-2007 the incidence of nervous system tumours increased significantly in the Gothenburg medical region, which seems to have better reporting than other medical regions in Sweden.…”
Section: Ci) --------------------------------------------------------mentioning
confidence: 99%